Supercondutividade no ensino médio: uma proposta fundamentada na aprendizagem baseada em problemas - Barbosa, Nara Gracy Travessa (2016)
This dissertation presents an insertion proposal of the Superconductivity in the Secondary Level Education, having as foundation the Learning Process Based on Problems (ABP). In the educational context, the teaching of Superconductivity, one of the Contemporary themes in Physics, turns out to be necessary for having a set of applications connected to the daily lives of students, what evidences the importance of its insertion in the Physics curriculum of the Secondary Level Education. For this insertion, it was used an ABP, due to its characteristics favoring the active participation of the students in the teaching and learning process. The ABP methodology has as central point a problem to be solved, and as a means of answering it presents seven ways in its structure, in which the students are the active subjects and the teacher accomplishes the role of tutor. With this foundation, the research has as general purpose to analyzes the implementation of a proposal to insert Superconductivity in the Secondary Level Education, having as methodological support the Learning Based on Problems, in view of the need to have the teaching of Physics more contextualized that allows students to list the scientific knowledge with the life. Therefore, it was used a qualitative nature research for presenting peculiar feature for the conduction of the research and for the obtained tract data. The implementation of the proposal, with 38 students of the Secondary Level Education from a public school in Manaus – AM, located in the West zone, it was organized in three stages: the presentation of superconductors application and the central problem to be solved; the application of a questionnaire to evaluate the previous knowledge of the students; the approach of each block of content and resolution of the central problem. For this last stage, the approach of the Superconductivity theme, was organized in six blocks of contents: Historical Context; Current and resistance; Zero Resistivity and effect Meissner; superconductor x perfect conductor; theory BCS; 6) types of superconductors. The analysis of its data started from the specifics problems resolution proposed in each block and the results showed that the insertion of Superconductivity in the Secondary Level Education, by means of the Learning Process Based on Problems, enabled the Physics teaching contextualized and that allowed students to list the scientific knowledge with the daily life.